S112 Variability in susceptibility to antibiotics and bacteriophages between individual colonies of Pseudomonas aeruginosa from cystic fibrosis sputum samples: implications for future clinical trial design. (12th November 2015) - Khoo, V; Pabary, R; Lund Palau, H; Turnbull, A; Madden, N; Schelenz, S; Jones, A; Morales, S; Alton, EWFW; Davies, JC
Abstract : Antimicrobial resistance is a growing problem. As part of the Cystic Fibrosis (CF) Trust-funded Strategic Research Centre for research into Pseudomonas aeruginosa (Pa) (http://www.cysticfibrosis.org.uk/research-care/research/about-cystic-fibrosis-research/how-we-invest-in-research/strategic-research-centres/src-1 ), we are exploring the therapeutic potential of bacteriophages. To date, we have a) identified a mix of 4 bacteriophages to which >80% of our CF isolates appear sensitive; b) confirmed efficacy in an acute murine model and c) confirmed compatibility with clinically relevant nebulisers. In the clinical trial, patients will be selected on the basis of confirmed sensitivity of their Pa strain (s) to the bacteriophage mix. Significant variability has previously been reported when multiple, morphologically indistinguishable colonies were tested against antibiotics; here, we explored whether a similar phenomenon occurs with bacteriophages. CF sputum (n = 6 patients) was cultured on Pa-specific agar. Up to 10 individual morphologically identical colonies were inoculated separately into broth. After overnight culture each was subjected to disc diffusion (12 antibiotics) and phage testing (standard plaque assays). Reproducibility (repeat testing of same broth) was excellent for susceptibility/resistance to antibiotics (97.2% within 3 mm) and bacteriophages (93.3% within one log dilution). Variability in antibiotic susceptibility was lower than anticipated: in no samples were there both completely resistant and fully sensitive colonies and although zone sizes did vary, these crossed break points in only 12.5% of assessable samples. There was more variability in phage sensitivity. Colonies from two subjects displayed <1 log dilution differences between them and were therefore reasonably consistent. The other 4 subjects displayed >1 log differences between the most and least sensitive; in one, colonies clearly fell into two groups (highly sensitive/less so with a 4 log dilution difference) and on subculture, differences in pigment production were apparent. Susceptibility may not be predicted by testing a mix of colonies. As described previously for antibiotics, individual, apparently morphologically similar colonies of Pa in a CF sputum sample display inconsistent susceptibility profiles to anti-pseudomonal bacteriophages. The potential role of genetic variability to explain this is being explored and numbers increased. The results may help determine the best methodology for assessing isolate susceptibility to a phage mix for inclusion in a future clinical trial.